Comparative Study of Crosstalk Reduction Techniques in RF Printed Circuit Board Using FDTD Method - Rajeswari Packianathan; Raju Srinivasan (International Journal of Antennas and Propagation)
Miniaturization of the feature size in modern electronic circuits results from placing interconnections in close proximity with a high packing density. As a result, coupling between the adjacent lines has increased significantly, causing crosstalk to become an important concern in high-performance circuit design. In certain applications, microstriplines may be used in printed circuit boards for propagating high-speed signals, rather than striplines. Here, the electromagnetic coupling effects are analyzed for various microstrip transmission line structures, namely, microstriplines with a guard trace, double stub microstriplines, and parallel serpentine microstriplines using the finite-difference time-domain method. The numerical results are compared with simulation results, where the variants are simulated using an Ansoft high-frequency structure simulator. The analysis and simulation results are experimentally validated by fabricating a prototype and establishing a good correspondence between them. Numerical results are compared with simulation and experimental results, showing that double stub microstriplines reduce the far end crosstalk by 7 dB and increase the near end crosstalk by about 2 dB compared with the parallel microstriplines. Parallel serpentine microstriplines reduce the far end crosstalk by more than 10 dB and also reduce more than 15 mV of peak far end crosstalk voltage, compared with parallel microstriplines.